Training, Incentives, and Malaria Cadre Performance: Examining the Mediating Role of Work Motivation - Jack Henry Syauta; Ricky Dwi Kurniawan (Lembaga Riset dan Inovasi Al-Matani, 2026)
Malaria remains a major public health challenge in Papua, where community-based control programs rely heavily on the effectiveness of malaria cadres. Although training and incentives are widely recognized as important human resource practices, previous findings regarding their influence on performance have been inconsistent, particularly in community health worker contexts. This study aims to examine the role of work motivation in explaining the relationship between training, incentives, and the performance of malaria cadres. A quantitative explanatory research design was employed using a census sampling approach involving malaria cadres participating in the PERDHAKI Malaria Program in Jayapura City. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that training and incentives positively contribute to cadre performance and also enhance work motivation, which subsequently supports improved performance outcomes. However, the mediating role of work motivation appears to be relatively limited, suggesting that cadre performance is influenced more strongly by direct structural and operational interventions than by indirect motivational mechanisms alone. This study contributes to the human resource management literature by demonstrating that the role of motivation as a mediator is context-dependent in community-based health programs. Practically, the findings highlight the importance of integrating field-oriented training, fair incentive systems, supervision, and motivational support to strengthen malaria cadre performance sustainably.